2012
DOI: 10.7205/milmed-d-11-00362
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship and Job Satisfaction Among Navy Family Physicians

Abstract: Having a mentor is associated with positive job satisfaction among Navy family physicians, even after adjusting for multiple other factors. An implication is that a mentorship program may be a strategy for improving job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…In the meantime, some studies have found significant gender differences. For example, Saperstein et al surveyed 186 Navy family physicians with one self-developed item, and found that males had more positive job satisfaction ( 16 ). While in 1,472 doctors from rural areas in West China, the authors reported that female doctors had better job satisfaction than males, based on a self-developed questionnaire ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, some studies have found significant gender differences. For example, Saperstein et al surveyed 186 Navy family physicians with one self-developed item, and found that males had more positive job satisfaction ( 16 ). While in 1,472 doctors from rural areas in West China, the authors reported that female doctors had better job satisfaction than males, based on a self-developed questionnaire ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined gender differences of job satisfaction in physicians. While some did not find significant gender differences (10)(11)(12)(13)(14)(15), and a few other studies even found the opposite, that male physician reported higher job satisfaction (16,17).…”
Section: Introductionmentioning
confidence: 93%
“…Research establishes objective benefits of mentoring in the military. Soldiers with a mentor showed earlier promotions, higher SAT scores, stronger career commitment, and lower (Carter et al, 2016;Saperstein, Viera, & Firnhaber, 2012). Additionally, mentored soldiers showed more incentive to become mentors later and continue supporting their less experienced comrades (Rieckhoff, Schleifer, & McCarthy, 2012).…”
Section: Mentoring In the Militarymentioning
confidence: 99%
“…[1][2][3][4] Because of these benefits, there is interest in creating formal mentoring programs within residencies. Optimal methods of developing mentoring relationships are not known.…”
Section: Introductionmentioning
confidence: 99%